RANCANG BANGUN SISTEM INFORMASI SPASIAL BERBASIS WEB PADA SEBARAN LOKASI TEMPAT PEMBUANGAN SEMENTARA SAMPAH KOTA - Zainul Arham (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2011)
The rapid growth of Tangerang city makes the requirements of facilities and infrastructures to support thisdevelopment also need attention. One of the technical operational problems of trash management in Tangerangis the unevenly distribution of TPS (Tempat Pembuangan Sementara_Garbage Disposal) for several districts.Therefore, it requires a geographical analysis toward the distribution of TPS in order that the Government ofTangerang city can make the appropriate decision in making the distribution of TPS and determining moreprecise locations in placing it. In designing the system, the researcher used the SDLC (System Development LifeCycle) method. The spatial data processing technology used the Arc View 3.3 and a PostgreSQL database. TheApplication of WebGIS in TPS deployment can help facilitate in analyzing the distribution of TPS in Tangerangand help facilitate the community in providing the proposed procurement of a new TPS